2002
DOI: 10.1002/pssc.200390067
|View full text |Cite
|
Sign up to set email alerts
|

Step‐Flow Growth of InN on N‐Polarity GaN Template by Molecular Beam Epitaxy with a Growth Rate of 1.3 μm/h

Abstract: The effects of substrate temperature and surface stoichiometry on the growth behavior of InN were investigated in molecular beam epitaxy with in situ monitoring by reflection high-energy electron diffraction and spectroscopic ellipsometry. InN was grown on nitrided sapphire substrate or N-polarity GaN template. For both cases, InN layers were found in N polarity by coaxial impact collision ion scattering spectroscopy. At growth temperatures ranging from 470 to 590 C, the N-rich condition was favorable for stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 5 publications
0
25
0
Order By: Relevance
“…It was estimated that the higher equilibrium vapour pressure of N and the lower decomposition temperature of InN lead to higher defect densities compared with AlN or GaN. It was found that the anion polarity crystal has higher quality [1]. Recently single crystals were found to have a bandgap energy below 1 eV.…”
mentioning
confidence: 97%
“…It was estimated that the higher equilibrium vapour pressure of N and the lower decomposition temperature of InN lead to higher defect densities compared with AlN or GaN. It was found that the anion polarity crystal has higher quality [1]. Recently single crystals were found to have a bandgap energy below 1 eV.…”
mentioning
confidence: 97%
“…Based on the indium compositional profile in In-rich InGaN layer, we calculated energy levels and envelope functions by Fourier series method in In-rich InGaN/ GaN SQW with compositional grading and we could explain nearultraviolet ͑UV͒ emission observed from the SQW. 10 We obtained In-rich InGaN/ GaN SQWs at relatively high growth temperature, compared with previous reports, [1][2][3][4] and at high TMIn flow rate. There existed thickness fluctuations and many structural defects in as-grown InGaN as well as in subsequently grown low temperature ͑LT͒-capped GaN.…”
Section: In-rich Ingan/ Gan Quantum Wells Grown By Metal-organic Chemmentioning
confidence: 70%
“…[1][2][3][4] Although thermal instability of InN as well as large lattice and thermal mismatches make the growth of high quality InN films extremely difficult, 5 more recent results on InN growth are strongly positive and indicative of potential device applications. 6,7 In this case, InN and In-rich nitrides are important constituents in devices such as light emitting diodes ͑LEDs͒, high electron mobility transistors ͑HEMTs͒, and solar cells so that the growth of two-dimensional ͑2D͒ InN and In-rich nitrides on GaN substrate is inevitable.…”
Section: In-rich Ingan/ Gan Quantum Wells Grown By Metal-organic Chemmentioning
confidence: 99%
“…Epitaxial layers were grown at 580-630 °C on an InN or GaN buffer layer grown around 450 °C. The nitrogen polarity was found by coaxial impact collision ion scattering spectroscopy (CAICISS) measurements [4]. Hall measurements were performed at room temperature (RT).…”
Section: Methodsmentioning
confidence: 99%